Effect of melatonin priming on seed germination, carbohydrate metabolism, and antioxidant system in Triticum aestivum (Poaceae) under drought and salt stress - Taraban D.A.; Karpets Yu.V.; Yastreb T.O.; Lugova A.A.; Pysarenko V.M.; Kolupaev Yu.E. (Ukrainian Botanical Journal)
Treatment of plants with melatonin (N-acetyl-5-methoxytryptamine, MT) can increase plant resistance to various abiotic stresses, including drought and salinity. However, the effect of melatonin priming of cereal grains, in particular of wheat, on their germination and the state of seedling defence systems under osmotic stress remains insufficiently studied, and this determined the aim of our research. The effect of incubating seeds in a melatonin solution at a concentration of 20 µM for 3 hours, followed by drying, on the germination of seeds of winter common wheat (Triticum aestivum 'Etana'), seedling growth, and the state of their antioxidant and osmoprotective systems under the influence of model drought (15% PEG with a molecular weight of 6000 Da) or salinity (150 mM NaCl) was evaluated. Under the influence of PEG 6000 and especially NaCl, a decrease in seed germination and inhibition of seedling growth were observed. Pretreatment of seeds with melatonin solutions significantly alleviated these effects. Stress factors caused a decrease in amylase activity in grains and sugar content in seedling shoots, and treatment of seeds with melatonin eliminated these effects. Melatonin priming also reduced the generation of reactive oxygen species (ROS) by seedling shoots and the accumulation of the lipid peroxidation product malondialdehyde (MDA) under stress conditions. The high positive correlation of seed germination and shoots growth with amylase activity, sugar content, and catalase activity indicates the contribution of changes in carbohydrate metabolism and the functioning of the antioxidant system to the stress-protective effect of melatonin. At the same time, proline content inversely correlated with germination of seeds and growth but directly correlated with ROS generation and MDA levels, which characterise the development of oxidative stress. It was concluded that melatonin priming of wheat seeds is promising for improving germination processes under adverse conditions.